Moved through music: The effect of experienced emotions on performers' movement characteristics. (March 2013) - Van Zijl, Anemone G. W.; Luck, Geoff
Do performers who feel sad move differently compared to those who express sadness? Although performers' expressive movements have been widely studied, little is known about how performers' experienced emotions affect such movements. To investigate this, we made 72 motion-capture recordings of eight violinists playing a melodic phrase in response to three different instructions. The first instruction was to focus on the technical aspects of playing. The second instruction was to give an expressive performance. Before the third instruction, performers were subjected to a mood induction task. Following this, performers played while focusing on their experienced emotions. After each playing condition, performers were interviewed about their thoughts and feelings. Analyses of the amount, speed, acceleration, and smoothness of movement revealed a different pattern of movement characteristics for each performance condition. In the expressive condition, the amount, speed, acceleration, and jerk of movement were highest. In the emotional condition, performers moved less, slower, and more smoothly. The findings of this exploratory study provide concrete evidence that performers' experienced emotions affect the movement characteristics of their performance.